2008
DOI: 10.1055/s-2007-1011931
|View full text |Cite
|
Sign up to set email alerts
|

Sonographische Milzgrößenbestimmung: Normalmaße beim milzgesunden Erwachsenen

Abstract: Sonography can rapidly and reliably help to determine the size by the spleen. To standardise the sonographic dimensions of the healthy spleen, we effected sonographic examination of 793 female and male patients aged between 17 and 82 years with a healthy spleen. In 95% of the patients the length of the spleen was less than 11 cm, the breadth below 7 cm and the thickness less than 5 cm. The weight of the spleen as determined via the rotation ellipsoid formula was below 190 g in 95% of the patients. Whether or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…in their study of a Chinese population suggested an upper limit of normal length of 12 cm. Some textbooks of ultrasound and other studies suggested an average splenic length of 12 cm, average width of 5 cm, and average depth (antero-posterior dimension) of 7 cm 122225. These observations suggest that there is no significant racial bias of spleen size in this study as compared with Caucasians.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…in their study of a Chinese population suggested an upper limit of normal length of 12 cm. Some textbooks of ultrasound and other studies suggested an average splenic length of 12 cm, average width of 5 cm, and average depth (antero-posterior dimension) of 7 cm 122225. These observations suggest that there is no significant racial bias of spleen size in this study as compared with Caucasians.…”
Section: Discussionsupporting
confidence: 57%
“…The intercostal spaces were used as scan window, for proper visualization of the entire spleen. All measurements were made on sections through the splenic hilum in order to create a constant reference point for repeating measurement according to the guidelines of the American Institute of Ultrasound in Medicine12 and as described by Lamb et al 19. Splenic length (the maximum distance between the dome of the spleen and the splenic tip) was done on the longitudinal section.…”
Section: Methodsmentioning
confidence: 99%
“…We also calculated the AST/ALT ratio. Splenomegaly was diagnosed when spleen length exceeded 12 cm at ultrasound examination (43). Alcohol consumption was defined as drinking more than 30 g per day of alcohol for at least 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…If a histological assessment was not available, liver cirrhosis was diagnosed based on clinical, laboratory, and imaging findings, comprising a platelet count of less than 100 000/μL, and ultrasound findings, which include a blunted nodular liver edge and splenomegaly (> 12 cm), the presence of varices, and complications of liver cirrhosis such as ascites and hepatic encephalopathy . Spleen diameter was measured using sonography or computed tomography (CT).…”
Section: Methodsmentioning
confidence: 99%